Differences in Labor Pain in the First Stage of the Active Phase Before and After Being Given Rebozo Shake The Apple Tree at TPMB Afah Fahmi, Surabaya City Area - Evi Agustina; Titi Maharrani; Nana Usnawati; Kharisma Kusumaningtyas (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2024)
Childbirth pain is a physical stimulus due to uterine contractions, dilatation and effacement of the cervix, as well as the descent of the fetus into the birth canal. The aim of the research was to determine the difference in labor pain during the first active phase before and after being given Rebozo shake the apple tree. Pre-experimental research design with a one group pretest posttest research design. A sample 35 women giving birth during the first active phase at TPMB Afah Fahmi using purposive sampling. The independent variable is rebozo shake the apple tree treatment. The dependent variable is pain during the first active phase. Using the Wong-Baker pain scale instrument. Wilcoxon signed rank test data analysis. The research results have a p-value of 0.000. So, there is a difference in labor pain during the first active phase before and after intervention is given. The rebozo shake the apple tree method can reduce labor pain during the first active phase. In conclusion, Rebozo shake the apple tree can reduce labor pain during the first active phase. It is recommended that this method be applied to reduce labor pain. However, further research needs to optimize pain assessment using other measuring scales.